PTH-062 Clinic based outpatient transnasal endoscopy:implementation and evaluation of an innovative endoscopy service. (8th June 2018) - Tewari, Nilanjana; Parra-Blanco, Adolfo; Sami, Sarmad; Budihal, Shiv; Lewis, Nina; Catton, James; Ragunath, Krish
Abstract : Introduction: There is increasing evidence that Transnasal endoscopy (TNE), performed with an ultrathin HD scope, is well tolerated with minimal cardiorespiratory stress and better patient experience than standard endoscopy. We report preliminary results from a new outpatient TNE service developed in a university teaching hospital which is a tertiary referral centre for gastroenterology and upper gastrointestinal surgery. Methods: After local governance approvals, TNE was introduced and performed by 5 experienced endoscopists. All procedures were performed in an outpatient clinic adjacent to the endoscopy recovery area over a 6 month period. Patients were assessed as suitable for TNE based on local guidelines and if agreeable, underwent TNE using Pentax EPK-i7000 HD video endoscopy processor and EG16-K10 Transnasal endoscope (outer diameter 5.4 mm, 2.0 mm instrument channel) under topical anaesthetic plus anti-congestant applied to nostril. An antifoam/mucolytic drink was given 15 min prior to procedure. If the nose could not be intubated, the patient was offered the procedure using the narrow endoscope trans-orally. Preliminary data was collected in a pilot study in which patients were asked to complete a visual analogue score (VAS) and questionnaire. Data on all patients undergoing TNE was collected prospectively and retrospectively analysed from the hospital computer records. Results: Since its introduction, 113 patients have been assessed as suitable for TNE. 67 females and 46 males (median age 62, IQR 52.5–70 years) underwent TNE. The first 17 patients were part of the pilot study. Of 96 subsequent patients, 66 were direct to test referrals on the cancer pathway, 10 other referrals on the cancer pathway, 13 routine, 3 planned surveillance, 1 urgent and 3 urgent inpatients. The most common indications were dysphagia (55 patients) and dyspepsia (36 patients). Endoscopy was completed trans-nasally in 92 patients (81.4%), trans-orally in 16 patients (14.1%) and failed in 5 patients (4.4%). Reasons for performing trans-orally were narrow nasal passages in 7 patients, 2 patients on warfarin with high INR, 2 patient choice and 7 didn't tolerate scope in nose. Duodenal intubation was successful in 107/113 (94.7%). There were no abnormal findings in 57 patients, inflammation was seen in 36 patients and 8 cancers of the oesophagus/oesophago-gastric junction were found. Biopsies were taken in 63 procedures and all were adequate for histology. Procedures were tolerated well with no immediate complications. Median (range) VAS was 9 (5–10) and of those who had had previous OGD, 71% expressed a preference for TNE and 29% preferred neither. Conclusions: TNE delivered in an outpatient clinic setting with immediate access to endoscopy unit is a safe and effective method of investigating upper gastrointestinal tract symptoms. This innovative service delivery has the potential to reduce traditional diagnostic gastroscopy and increase capacity.